2019
DOI: 10.3390/cryst9120630
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Phase Transitions in Sesquioxides

Abstract: Pressure is an important thermodynamic parameter, allowing the increase of matter density by reducing interatomic distances that result in a change of interatomic interactions. In this context, the long range in which pressure can be changed (over six orders of magnitude with respect to room pressure) may induce structural changes at a much larger extent than those found by changing temperature or chemical composition. In this article, we review the pressure-induced phase transitions of most sesquioxides, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 254 publications
(336 reference statements)
3
19
0
Order By: Relevance
“…In this way, we have shown a general overview of the behavior of RE SOs under compression that complements the one recently reported for phase transition pressures. 15 Moreover, we have extended the discussion regarding the linear dependence of the unit-cell volume and bulk moduli of RE SOs (including Sc 2 O 3 and Y 2 O 3 ) vs the cube cation ionic size to other C-type/bixbyite-type SOs. On top of that, we have found that our experimental bulk moduli for the different phases of Tb 2 O 3 are within the error margin of measurements, likely being the experimental bulk modulus of A-type Tb 2 O 3 being slightly underestimated.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In this way, we have shown a general overview of the behavior of RE SOs under compression that complements the one recently reported for phase transition pressures. 15 Moreover, we have extended the discussion regarding the linear dependence of the unit-cell volume and bulk moduli of RE SOs (including Sc 2 O 3 and Y 2 O 3 ) vs the cube cation ionic size to other C-type/bixbyite-type SOs. On top of that, we have found that our experimental bulk moduli for the different phases of Tb 2 O 3 are within the error margin of measurements, likely being the experimental bulk modulus of A-type Tb 2 O 3 being slightly underestimated.…”
Section: Resultsmentioning
confidence: 81%
“…These values are also in good agreement with the PT pressures reported in other RE SOs. 15 The XRD peaks of the A-type phase show up in the scans up to the maximum pressure of the experiment (20 GPa). Although these reflections could also be indexed with the H-type phase, RS measurements (see below) confirm that the phase above 12.0 GPa corresponds to the A-type structure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…One of the methods that can be used to obtain new polymorphs is exposing the molecular crystals to high-pressure in order to induce the phase transition [1]. Many studies deal with the experimental pressure-induced polymorphic transformations in molecular solids [2][3][4], in some cases the high-pressure polymorph may have the same space group symmetry as the original ambient-pressure form and even be isostructural with it, which is defined as isosymmetric phase transition [5,6]. However, in most cases the polymorphic phase transition is accompanied with the change of not only cell dimensions but also the crystal space group.…”
Section: Molecular Modeling Of Pressure Induced Phase Transitionmentioning
confidence: 99%
“…In their recent article, Prof. Manjon et al [13] conduct an extensive review of the progress they have made in recent years on pressure-induced phase transition in sexquioxides. These compounds constitute a large subfamily of ABO 3 -type compounds, which have many different crystal structures due to their large diversity of chemical compositions.…”
mentioning
confidence: 99%